COMPARISON OF EARLY CHILDHOOD EDUCATION PLAY ENVIRONMENT DESIGN MANAGEMENT AT RA BABUSSALAM AND RA RAUDHATUL HASANAH SUNGGAL SUB-DISTRICT MEDAN SUNGGAL SUB-DISTRICT MEDAN CITY - Rahayu Dwi Utami; Novalinda Novalinda; Putri Utami (Proceeding International Seminar of Islamic Studies, 2023)
Early Childhood Education play environment design management is expected to design an early childhood education play environment well with the aim of educational achievement in the school environment. The Early Childhood Education play environment needs to be arranged in such a way that this will have a major impact on the growth and development of early childhood so that children have the readiness to continue to the next education, the precise arrangement of indoor and outdoor display set plans. Although the activity of designing indoor and outdoor appearances. The fantasy world of early childhood has a major influence on the optimal development of religious and moral values, language, cognitive, social-emotional, and physical motor. The purpose of this study was to find out how the management of the design of the play environment of early childhood education in RA Babussalam and RA Raudhatul Jannah. This research uses qualitative methods. Data collection techniques are carried out through interviews, observation, documentation research and triangulation. The results of this study show that the management of early childhood education environment design both indoor and outdoor in RA Babussalam and RA Raudhatul Hasanah is still not carried out properly. Because it adjusts the condition of the school with a building that is not so spacious. Therefore, not all facilities have been realized. However, the functions of planning, organizing, mobilizing and supervising are carried out by the institution. The utilization of indoor and outdoor facilities at RA Babussalam and RA Raudhatul Hasanah is quite maximal. Where the learning process always utilizes existing facilities. That way also maintain and take good care of the facilities that have been owned.